IMPLEMENTASI MODEL PEMBELAJARAN DISCOVERY LEARNING SEBAGAI UPAYA PENCEGAHAN PERILAKU BULLYING MELALUI PEMBELAJARAN AQIDAH AKHLAK KELAS 5 MI PADAMULYA DI DESA PADMULYA KECAMATAN CIHAURBEUTI KABUPATEN CIAMIS - Mahmudin, Wildan; M. Hasbi Assidiqi (Asatidzuna | Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Learning Aqidah Akhlak is a subject that has an important role in developing students' moral, ethical and spiritual values. However, the current challenge for teachers is to help students understand and apply moral, ethical and spiritual values ​​in everyday life. These problems include a lack of student involvement, teachers' difficulties in motivating students, as well as limitations in developing a deep understanding and application of the values ​​learned. The negative impact of this lack of moral learning is bullying. Using interesting and fun learning methods will greatly influence the learning atmosphere in the class. To overcome this, teachers need a strategy in the learning process, namely by implementing an appropriate learning method or model continuity of a good learning process. One of them is by using the discovery learning learning model. The purpose of this research is to determine: (1) Bullying behavior of fifth grade students before using the Discovery Learning learning model in teaching Aqidah Akhlak. (2) Implementation of the discovery learning learning model in the Moral Aqidah subject in an effort to prevent bullying in class V, MI Padamulya, Padamulya Village, Cihaurbeuti District, Tasikmalaya Regency (3) Bullying behavior of class V students after using the Discovery Learning learning model in learning the Aqidah Akhlak. This research is a type of qualitative research. The research subjects were moral aqidah subject teachers and class V students at MI Padamulya. The learning model used is the discovery learning model in the subject of moral beliefs. The instruments used for data collection were observation, interviews and documentation. The results of the research instrument will later be analyzed descriptively qualitatively. The results of this research show: (1) Students' attitudes before implementing the Discovery Learning learning model in Aqidah Akhlak learning still do not pay enough attention to the comfort of fellow students when learning, for example with attitudes that do not respect each other, corner each other, or even make fun of friends who have not dared to come forward. front of class. (2) implementation is divided into 3 stages, preliminary stage; the teacher opens the lesson with greetings, conveying the learning objectives, and apperception, the content stage; carried out by providing stimulus, problem identification, data collection, data processing, verification and generalization, closing stage; The teacher closes the lesson by appreciating the students' performance followed by providing closing motivation. (3) After implementing the Discovery Learning Learning Model in teaching Aakidah Akhlak to class V students with the results of learning evaluation using 3 assessments; attitude assessment, knowledge assessment, and research skills. Children can respect fellow friends or teachers more when studying, provide support or trust to friends well, and treat everyone well regardless of anything. Therefore, the accompanying teachers for subjects, especially moral beliefs, work together to provide guidance and teaching, especially in the field of beliefs and morals, in order to be able to prevent and minimize the occurrence of bullying behavior in the school environment, especially in MI Padamulya, Padamulya Village, Padamulya District, Ciamis Regency.